Implementasi Sistem Informasi Masjid (Simas) Kemenag Sebagai Instrumen Penguatan Good Governance dalam Pelayanan Masyarakat di Kabupaten Bogor - Herliansyah, Muhammad Rudy; Rita Rahmawati; Muhammad Luthfie (Jurnal Administrasi dan Kebijakan Publik, 2025)
This study explores the implementation of the Ministry of Religious Affairs’ Mosque Information System (SIMAS) as a tool to strengthen good governance in mosque management within Bogor Regency. Despite increasing digitalization in public services, the application of such systems in religious institutions remains under-examined. This research addresses this gap by analyzing how SIMAS contributes to improving transparency, accountability, participation, responsiveness, and fairness in mosque governance. The study aims to describe the operationalization of SIMAS, identify factors that enable or hinder its success, and evaluate its effectiveness in supporting mosque administration. Using a qualitative approach, data were collected through interviews and direct observations to capture the perspectives of stakeholders involved in SIMAS implementation.Findings indicate that SIMAS positively influences governance by promoting more open, responsive, and participatory mosque management. These improvements are vital for aligning religious service delivery with broader good governance principles. The study also offers practical recommendations for the Ministry of Religious Affairs and mosque administrators to enhance system performance and public service outcomes.Theoretically, the research contributes to public administration literature by extending Van Meter and Van Horn’s policy implementation model. It introduces three additional dimensions sustainability, monitoring and evaluation, and innovation which are crucial for understanding the long-term success of digital governance tools in religious and public institutions.